2014
DOI: 10.1364/josaa.31.000603
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of Bessel and Airy beams through atmospheric turbulence

Abstract: We investigate, through simulation, the modifications to Bessel and Airy beams during propagation through atmospheric turbulence. We find that atmospheric turbulence disrupts the quasi-non-diffracting nature of Bessel and Airy beams when the transverse coherence length (Fried parameter) nears the initial aperture diameter or diagonal respectively. The turbulence induced transverse phase distortion limits the effectiveness of Bessel and Airy beams for applications requiring propagation over long distances in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(50 citation statements)
references
References 22 publications
3
46
0
1
Order By: Relevance
“…These results are in line with other authors simulations such as Nelson et al [11] who showed that the turbulence disrupts the ring structure of the Bessel beams and that the best power transmission is when that Bessel beam has no rings at all as in our case. In their paper they describe this case as a truncated Gaussian beam.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are in line with other authors simulations such as Nelson et al [11] who showed that the turbulence disrupts the ring structure of the Bessel beams and that the best power transmission is when that Bessel beam has no rings at all as in our case. In their paper they describe this case as a truncated Gaussian beam.…”
Section: Discussionsupporting
confidence: 94%
“…In this paper we simulate the propagation of both Gaussian and Bessel beams from ground level, through atmospheric turbulence. Previously, Nelson et al [11] investigated the propagation of these beams within a short ground-to-ground range of 6.4km, with constant strength of turbulence. They showed how the ring structure is disrupted by the atmosphere and that there is an increasing on axis intensity loss with an increasing number of rings.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, we include the case of monochromatic, phase matched tiles. Following our previous work [12], we propagate the beam by numerically solving the paraxial wave equation. Atmospheric turbulence is modeled as phase screens located at discrete locations along the z-axis.…”
Section: Propagation In Turbulent Atmospherementioning
confidence: 99%
“…Atmospheric turbulence is modeled as phase screens located at discrete locations along the z-axis. For details on the split-step phase screen simulation see [12]. , as a function of bucket radius for the incoherently combined beam (blue), coherently combined beam (green), and phase matched monochromatic beam (red).…”
Section: Propagation In Turbulent Atmospherementioning
confidence: 99%
“…Such beams allow variations of their transverse diffraction pattern along the optical axis to be controlled. The practical significance of the nondiffracting beams stems from their ability to show stability during propagation in a turbulent atmosphere [10], whereas femtosecond Bessel pulses preserve their shape as they propagate [11].…”
Section: Introductionmentioning
confidence: 99%